Nested scales of sustainable livelihoods: Gendered perspectives on small-scale dairy development in Kenya - Basu, P.; Galiè, Alessandra (MDPI, 2021)
The sustainability of rural development programs has often been conceptualized through the Sustainable Livelihoods Framework, or SLF. This article utilizes the SLF to examine the outcomes of small-scale dairy development in western Kenya and thus connect local perspectives on livelihoods with broader ideas of sustainable livelihoods. Drawing on individual interviews conducted with farmers in three dairy development sites in western Kenya, it examines compatibilities and contradictions between productivity and sustainability, and how gender becomes a vantage point from which the links between micro- and macro-sites, or nested scales of sustainable livelihoods, become visible. Three main kinds of benefits related to dairy development are identified by respondents: increase in income, access to market, and ability to keep improved cattle. In conjunction with these benefits, respondents identified problems related to women’s independent access to income, wider community consumption of milk, and lack of infrastructure, respectively. This study thus shows that while income and productivity is prized by all respondents, gender enables this broader goal to be viewed in more nuanced terms—not only within the household, but also through links between the household and the wider community and state. Gender thus becomes salient across the nested scales of sustainable livelihoods and provides insights into how a more encompassing notion of sustainable livelihoods can be implemented.